Cloaking a concentrator in thermal conduction via topology optimization. (October 2020) - Fujii, Garuda; Akimoto, Youhei
Highlights: Topology optimization for thermal cloak-concentrator is proposed based on the level set method and CMA-ES. Simultaneous realization of cloaking and concentrating of heat flux is achieved. Structural characteristics needed for simultaneous cloaking and concentrating are revealed. Thermal cloakconcentrator that is robust against fluctuations of thermal conductivity is designed. Graphical abstract: Abstract: The simultaneous cloaking and concentrating of heat flux is achieved through topology optimization based on a covariance matrix adaptation evolution strategy by formulating the optimization problem of improving two different objective functions. The topology-optimized thermal cloak–concentrator realizes excellent bi-functionality (i.e., cloaking and concentrating) despite having a simple composition, and structural characteristics needed for simultaneous cloaking and concentrating are revealed adopting a level set method with clear structural interfaces. Moreover, a thermal cloak–concentrator that is robust against fluctuations of thermal conductivity is designed by improving a fitness incorporating multiple objective functions under various thermal conductivities.